Pelaporan Keuangan Sederhana bagi UMKM KSBI - Lestari, Henny Setyo; Martiningtiyas, Catur Rahayu; Ekasari, Ayu; Laksono, Wafi Suryo; Ardelia, Rahmadina (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
The implementation of this PkM activity aims to provide training to help MSMEs improve their skills in simple digital-based financial recording in order to face competition in the industrial era 4.0. The implementation of this PkM activity was held on November 30, 2024 at the Indonesian Community Success Community (KSBI) MSME. Participants in this PkM activity were 19 active MSME actors engaged in the culinary, service and trade sectors. The initial activity was to conduct financial literacy in the form of a basic financial education workshop tailored to the needs of MSMEs. The material presented included an introduction to basic financial elements such as transaction recording, cash flow management, and the preparation of simple reports. Increasing efforts in understanding and using digital technology for financial recording was carried out through training activities focused on the introduction and guidance for using Android and Cloud-based accounting applications that were user-friendly and easy to learn. Participants who were previously unfamiliar with recording simple transactions, but after the training were able to prepare financial reports and record transactions more systematically. The results of the practice showed that approximately 75% of participants successfully prepared simple financial reports. Participant satisfaction was also high, with 85% stating that the material was highly relevant to their business needs.